Anglican missionary policy in the diocese of Grahamstown under the first two bishops, 1853-1871 - Goedhals, Mary Mandeville (Rhodes University, Faculty of Divinity, Department of Divinity, 1979)
In 1843 a committee of the Colonial Bishroprics Fund appointed to investigate the state of the Church of England at the Cape of Good Hope, recommended the formation of a bishopric, and suggested that the bishop settle in the eastern districts of the colony, with an archdeacon in Cape Town. Three significant principles had been enunciated: the church was to grow under a bishop, the church would have a dual mission to blacks and whites, and the colony's eastern frontier, long a political and military headache, was seen as the focus of a new and spiritual battle. Contact between Nguni tribesmen and the eastward-moving European trekboer began in the region of the Fish River during the rule of the Dutch East India Company. Cattle and land were the main ingredients of the frontier conflict. From the point of view of the white settler, the growing cattle trade meant an increased need for pasture, but although the motive for expansion was economic, frontiersmen had come to regard large lands as their birthright. The semi-nomadic pastoral economy of the Nguni also required abundance of land, which was vested in the tribe. To the tribesmen, their cattle had a political, social and religious significance which transcended the economic. Cattle were sacrificed to the ancestors to propitiate the shades of the departed and to secure the prosperity of the tribe. The years of conflict, the constant threat to their herds and their land, undermined the basis of Nguni society, without providing it with a new foundation.
Keywords: Church of England -- Dioceses -- South Africa -- Grahamstown; Bishops -- South Africa -- Grahamstown; South Africa -- History -- Xhosa Cattle-Killing, 1856-1857; South Africa -- History -- 1836-1909; Education -- South Africa -- History -- 19th century; Black people -- South Africa -- 19th century; Armstrong, John, 1813-1856; Cotterill, Henry, 1812-1886